Differences In The Effectiveness Of Giving Tomato Juice And Cucumber Juice In Lowering Blood Pressure In Hypertension In The Review Of Pregnancy - Iyos Rosnawati; Mahyar Suara (CV. Inara, 2024)
Background the content of tomato and cucumber juice both contain potassium which functions as a catalyst so that potassium can play a role in lowering a person's blood pressure. The purpose of writing: to determine the difference in the effectiveness of giving tomato juice and cucumber juice in reducing blood pressure in those who experience hypertension in terms of gestational age. Research Methods: Pre-experimental research with the type of one group pre test – post test design by means of a causal relationship by involving one group of subjects. the subject group was observed before the intervention was carried out and then observed after the intervention was carried out. The sampling technique is non-probability sampling with a purposive method. The study was divided into 2 variables, namely the independent variables, namely the consumption of tomato juice and cucumber juice. Research Results: The results of statistical tests are known Asymp. Sig (2 – Talled) has a value of 0.263, because 0.263 > 0.05, it can be concluded that the hypothesis is rejected. This means that there is no difference in giving tomato juice and cucumber juice in reducing blood pressure in those with hypertension. This means that tomato juice and cucumber juice both have the same efficacy in reducing blood pressure in pregnant women. However, from the Mann –Whitney mean rank between giving tomato juice and cucumber juice, it was found that cucumber juice was more effective than tomato juice in reducing blood pressure. Conclusions and Suggestions: The results of this study are expected to provide information that giving date palm juice and beetroot juice is a type of natural food that can increase Hb levels.